Heterozygous CYP27B1 c.262delG pathogenic variant and its impact on vitamin D metabolites and phosphocalcic profile in humans - Girard, Lysanne; Fortin, Carol-Ann; Plourde, Rosalie; Desgagné, Véronique; Guérin, Renée; Albert, Caroline; Desmeules, Mathieu; Perron, Patrice; Bouchard, Luigi (Frontiers in Physiology, 2026)
Background/aimsVitamin D-dependent rickets type 1A is a rare autosomal recessive disorder caused by pathogenic variants in the CYP27B1 gene. CYP27B1 encodes for the 1α-hydroxylase enzyme catalyzing the conversion of 25-hydroxyvitamin D (25(OH)D) to calcitriol, the last step of vitamin D activation. In the Saguenay–Lac-Saint-Jean (SLSJ) region (Quebec, Canada), the CYP27B1 c.262delG variant has a carrier rate of 1 in 27 due to a founder effect. This study aimed to characterize the impact of heterozygosity for the CYP27B1 c.262delG variant on vitamin D metabolites and the phosphocalcic profile.MethodsParticipants from SLSJ were recruited by telephone (n = 36). During an in-person visit, buccal swabs, blood samples, and health and lifestyle information were collected. The CYP27B1 c.262delG variant was genotyped using TaqMan assays on DNA from buccal swabs, and participants were grouped as carriers (heterozygous for the variant) and non-carriers. Student’s t-test was applied to compare vitamin D metabolites (25(OH)D and calcitriol), parathormone, alkaline phosphatase (ALP), bone alkaline phosphatase (BAP), ionized calcium, and inorganic phosphorus blood levels between carriers and non-carriers.ResultsCarriers showed significantly higher levels of parathormone, ALP, and BAP compared to non-carriers (p < 0.05). Additionally, 25(OH)D levels were higher in carriers, although the difference did not reach nominal statistical significance (p = 0.056). Calcitriol, ionized calcium, and inorganic phosphorus levels were similar between groups.ConclusionHeterozygosity for CYP27B1 c.262delG leads to changes on the vitamin D metabolites and the phosphocalcic profile. How these changes impact the risk of other vitamin D deficiency-associated conditions remain unknown.